2018
DOI: 10.1002/pbc.27235
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent and young adult oncology patients in France: Heterogeneity in pathways of care

Abstract: In France, pathways of care for AYAs are heterogeneous. It is necessary to organize a national network of expert centers with adequate medical skills and specific psychosocial support and facilities to provide the best possible care for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
(55 reference statements)
0
5
0
1
Order By: Relevance
“…Ferrari et al (n=575) established that children over 10 years old had a longer total interval than those younger than 10 years old 67. Desandes et al (n=43) found the same result when comparing age groups 15–19 vs 20–24 years (15.4 vs 48.7 weeks; p=0.04) 35. Smolle et al found no difference for patients with synovial sarcoma older or younger than 16 years old 68.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Ferrari et al (n=575) established that children over 10 years old had a longer total interval than those younger than 10 years old 67. Desandes et al (n=43) found the same result when comparing age groups 15–19 vs 20–24 years (15.4 vs 48.7 weeks; p=0.04) 35. Smolle et al found no difference for patients with synovial sarcoma older or younger than 16 years old 68.…”
Section: Resultsmentioning
confidence: 92%
“…Six studies reported a significantly longer total interval for older teenagers, adolescents or adults compared with younger children or (younger) teenagers (<12 vs ≥12–22 years1122; <20 vs ≥20–86 years26; <22 vs ≥22 years27; 0–14 vs 15–19 vs 20–29 years40; <12 versus ≥12 years11). Furthermore, Desandes et al found young adults were more at risk for a longer total interval than patients in puberty (15–19 vs 20–24 years; 10.1 vs 21.4 weeks respectively; p=0.04) 35. Lawrenz et al (n=1792) investigated age (mean 30.7 years) as a continuous variable and reported every additional year of age was associated with a 1.3 weeks longer total interval (p<0.00) 41.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dans un contexte de parcours de soins des AJA qui reste hétérogène (certains étant pris en charge en hématologie-oncologie pédiatrique, d'autres dans des services de médecine adulte) [1,3], nous avons étudié l'accès à la préservation de la fertilité des AJA atteints de pathologies cancéreuses au CHU de Clermont-Ferrand sur une période de 3 ans.…”
Section: Introductionunclassified